Analysis of development factors and by-products of small towns – case study of the town of Chojnice (Poland) - Miszewski, Fabian (Journal for Geography, 2025)
Small towns constitute a vital component of the local economy. However, they currently face numerous challenges related to demographic trends, urban investments, and the availability of local products. The town of Chojnice in Poland was selected as a case study for the research on the development factors of small towns and their by-products. Methods such as SWOT analysis were applied to assess development factors and local products, while the role of resources in creating by-products was also evaluated. The results indicate that Chojnice is experiencing a demographic crisis, while its unique geographical location presents both an advantage and a disadvantage.
Keywords: small towns; territorial marketing; small-town development; social factors; economic factors; environmental factors